Risk factors of cardiovascular diseases in paramedics - Rębak, Dorota; Suliga, Edyta; Głuszek-Osuch, Martyna; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2017)
Introduction : Cardiovascular diseases are the most life-threatening in Poland and constitute the most frequent cause of death. Aim of the research : The evaluation of the frequency of the occurrence of cardiovascular disease risk factors among paramedics of the ŚCRMiTS (Świętokrzyskie Centre of Emergency Medical Services) in Kielce. Material and methods : The subject study group involved 140 paramedics of the ŚCRMiTS in Kielce, excluding the doctors. The evaluation of their condition of health included the following measurements: blood pressure, biochemical analyses: fasting lipidogram, fasting glycaemia, anthropometric measurements, and a questionnaire interview. Results : The average body mass index of the group was above the norm and equalled 28.2 ±4.1 kg/m 2 . The average blood pressure equalled: systolic – 133.8 ±14.9 mm Hg, diastolic – 83.1 ±9.2 mm Hg. The average fasting glucose concentration was 95 ±33.8 mg/dl in the subject population. The average total cholesterol concentration of the group was 198.6 ±36.6 mg/dl, high-density lipoprotein fraction concentration – 48.4 ±10.5 mg/dl, low-density lipoprotein fraction – 121 ±33.8 mg/dl, triglycerides concentration – 168.9 ±120.7 mg/dl. Fifteen risk factors were analysed altogether. Conclusions : Cardiovascular disease risk factors are a significant risk for the subject group of paramedics and they generate a disadvantageous picture of a health profile. A vast majority of the subjects had an abnormal body mass, exceeded values of blood pressure, and had bad lipidogram parameters. The spread of risk factors and the degree of exceeding reference norms increases with age. It would be justified to prepare preventive measures aimed mainly at the reduction of body weight and the decrease of other modifiable risk factors for cardiovascular diseases.